The Relationship Between Ossification in Metacarpophalangeal Sesamoids of the Thumb and the Period of Puberty: A Radiographic Study - Rifat SAHIN; Cengiz KAZDAL (Medeniyet Medical Journal)
Objective: The current study aimed to determine the onset of sesamoid bones (Sbs) ossification at the thumb metacarpophalangeal (MCP) joint of the hand and its relationship with puberty. Methods: This retrospective radiographic study included patients aged 5-17 years. The presence of Sbs was investigated separately for each age group. Patients were classified based on their age, gender, and the presence of radial and ulnar sesamoids. Results: A total of 1,020 radiographs from 939 patients were analyzed. Sbs began to ossify in girls at the age of 8 years and in boys at the age of 9 years. The ulnar-radial sesamoids were present in all individuals in the same age group at the age of 13-14 years in girls and 15 years in boys. The age at which 50% of the individuals in the same age group had a sesamoid was 10.4 years in girls and 11.9 years in boys on the radial side, 9.5 years in girls, and 11.5 years in boys on the ulnar side. Conclusions: In all individuals, the time between the onset of sesamoids of the MCP joint and development corresponds to the physiological period of puberty. However, the age at which puberty begins coincides with the time when Sbs begin to ossify in 50% of both sexes in the same age group.